Analisis Framing Berita Bullying Pada Siswa SMP Cilacap di detik.com (Analisis Zhondang Pan dan Gerald M. Kosicki) - Putra, Muhammad Hidayat; Gustia, Arifah Yenni (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2023)
This research investigates how detik.com, an online media, frames news about bullying cases that occur among junior high school students in Cilacap. This qualitative research has a descriptive design. Data processing uses framing analysis – using Zhondang Pan and Gerald M. Kosicki’s framing model – which looks at four framing elements in a news story. This research investigates three categories of news on detik.com on 27,29 September 2023 and 2 Oktober 2023. Based on this research, detik.com used the inverted pyramid technique in reporting cases of harassment at Cilacap Middle School. The first of the news displays the main discussion topic. Apart from that, news writers obtain some data from sources’ statements. The news structure uses 5W + 1H and there are not many quotes from sources.